Measurement and interpretation of electrocardiographic QT intervals in murine hearts - Zhang, Yanmin (American Physiological Society, 2014)
Alterations in ECG QT intervals correlate with the risk of potentially fatal arrhythmias, for which transgenic murine hearts are becoming increasingly useful experimental models. However, QT intervals are poorly defined in murine ECGs. As a consequence, several different techniques have been used to measure murine QT intervals. The present work develops a consistent measure of the murine QT interval that correlates with changes in the duration of ventricular myocyte action potentials (APs). Volume-conducted ECGs were compared with simultaneously recorded APs, obtained using floating intracellular microelectrodes in Langendorff-perfused mouse hearts. QT intervals were measured from the onset of the QRS complex. The interval, Q-APR(90), measured to the time at 90% AP recovery, was compared with two measures of the QT interval. QT1 was measured to the recovery of the ECG trace to the isoelectric baseline for entirely positive T-waves or to the trough of any negative T-wave undershoot. QT2—used extensively in previous studies—was measured to the return of any ECG trough to the isoelectric baseline. QT1, but not QT2, closely correlated with changes in Q-APR(90). These findings were confirmed over a range of pacing rates, in low K(+) concentration solutions, and in Scn5a+/ΔKPQ hearts used to model human long QT syndrome. Application of this method in whole anesthetized mice similarly demonstrated a prolonged corrected QT (QTc) in Scn5a+/ΔKPQ hearts. We therefore describe a robust method for the determination of QT and QTc intervals that correlate with the duration of ventricular myocyte APs in murine hearts.